Zbieranie danych o nieletnim w praktyce polskich sądów - Włodarczyk-Madejska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The model of proceeding with juveniles applicable in Poland assumes an in-depth knowledge of a juvenile. Knowing this allows us to make an accurate diagnosis, and thus to react in the right way. How does the court get to know a juvenile? How often do supporting institutions engage in this process? How does he assess evidence in the form of an environmental interview or a diagnostic opinion, and which one is used in the process of adjudication? I provide answers to these questions in this article. The basis for their granting were the results of my own research carried out in 2015–2016 at two institutions: Department of Criminology, Institute of Law Studies of the Polish Academy of Sciences and the Institute of Justice. These were both the research of juvenile case files and surveys of representatives of the judiciary — a nationwide survey and individual semi-structured qualitative interviews.
Keywords: nieletni; sądy dla nieletnich; instytucje wspierające; wywiady środowiskowe; opinie diagnostyczne